Women's retention on the continuum of maternal care pathway in west Gojjam zone, Ethiopia: multilevel analysis - Amanu Aragaw Emiru; Getu Degu Alene; Gurmesa Tura Debelew (BMC, 2020)
Abstract Background The continuum of maternal care has been one of the effective approaches for improving the health of mothers and newborns. Although large numbers of Ethiopian women do not use maternal health services, points of drop out along the continuum are not understood well. Understanding of a particular point of maternal care dropout on the continuum, however, helps governments make effective interventions. This study aimed to assess the extent of women's service utilization and the factors affecting retention on the continuum of care in West Gojjam Zone, Ethiopia. Methods A community-based study linked to health facility data was conducted in June 2018. Data were obtained from 1281 mothers who gave birth to their last baby within the preceding 12 months from a two-stage cluster sampling. Data were collected via face-to-face interviews using a pretested questionnaire. Multilevel logistic regression models were used to examine the effects of individual and cluster-level factors on key elements of the continuum of care. The measure of fixed effects was expressed as Odds Ratio with 95% confidence interval. Results The study revealed that only 12.1% of women completed the continuum of maternal care services (ANC4+, SBA, and PNC within 2 days after birth); while 25.1% of them did not receive any care during their recent births. There were commonalities and differences in the predictors of the three indicators of maternal health service utilization. Variables related to services received during antenatal care such as early initiation of ANC (AOR = 7.53, 95%CI, 2.94, 19.29) and receiving proper contents (AOR = 3.31, 95%CI, 1.08, 10.16) were among the predictors significantly associated with the completion of the continuum of care. Conclusions The continuum of maternal care completion rate was extremely low, indicating that women were not getting the maximum possible health benefit from existing health services. The results also revealed that maternal health service utilization was influenced by factors operating at various levels-individual, household, community, and health facility. Since antenatal care is considered an entry point for the subsequent use of maternal services, strategies that aimed to improve maternal health service utilization should target early initiation and antenatal care quality.